Cooperative controversy technique to improve students’ motivation in English debate - Suciati Suciati (Journal on English as a Foreign Language, 2016)
Many students do not like English debate. They argue that in the debate, they should apply four skills in English and should have appropriate matter, manner, and method. One of the reasons which make them do not like the debate is their lack of motivation. To solve this problem, teacher or lecturer should apply the appropriate technique in the teaching-learning process. Cooperative controversy technique is different with the traditional debate. In this technique, debaters change positions and try to reach a consensus at the end of the debate. By doing it before practicing the real English debate format, the students will get the basic knowledge about the debate so they do not directly practice the complicated one. Cooperative controversy increases the number of ideas, quality of ideas, feelings of stimulation, and enjoyment and originality of expression in creative problem solving. If it is compared to the group which does not use controversy, in controversy, the members get motivation and satisfaction in solving the problems.